Rancang Bangun Sistem E-Surat Pada Desa Jungai Kecamatan Rambang Kapak Tengah - Sindi Andani; Andi Christian; Muchlis Muchlis (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
A letter is a means of written communication written on behalf of a person or on behalf of the organization used to convey the information to the intended party who has the need for the activity, whether for the need individual or organizational needs. Jungai village is one of the villages located in the District of Rambang Kapak Tengah. Correspondence activities in the Village Jungai has not been well accommodated such as complicated data storage, the problem of finding documents takes a long time. In contrast, the current village apparatus required to be able to work quickly, precisely and accurately, but it has not been provided applications that can accommodate correspondence activities. In doing This research uses qualitative research whose aim is to describe what is currently in effect. So that data will be obtained which supports the preparation of research reports. Meanwhile in this research The method used by the author is a qualitative descriptive method is a research method that utilizes qualitative data and explained descriptively with the aim of describing or explaining results from existing research. Software development methods The author uses the Waterfall model. Meanwhile, analysis tools and designing using UML (Unified Modeling Language) consists of use case diagrams, class diagrams and activity diagrams. This application can provide convenience for people with circumstances or conditions that are currently impossible came directly to the Jungai Village office to make a letter.